Compact Near Field Wireless Energy Transfer Systems Using Defected Ground Structures - Filipe Ferreira; Max Feldman; Giovani Bulla; Valner Brusamarello; Ivan Muller (IEEE Journal of Microwaves, 2023)
Near-Field Wireless Power Transfer systems have attracted attention for their potential applications, such as implanted medical devices, radio frequency identification, and portable electronic devices in general. In this context, a compact model for short-range NF-WPT systems operating in ISM frequency bands is proposed, employing the concept of ground plane aperture resonators or Defected Ground Structures (DGS). This technique allows the miniaturization of the resonator, which leads to the development of compact NF-WPT systems. The model proposed in this work aims at possible applications that require simultaneous energy and data transfer. This model operates in dual band in 433 MHz and 900 MHz frequency bands and makes use of overlapping circular DGS in order to shrink the resonator device and obtain high values of Figure of Merit (FoM) commonly used in this research area. The proposed model was designed using the electromagnetic analysis and built using Rogers RO4003 dielectric material. The designed dual-band DGS resonators have a total area of 11.7 × 10.2 mm $^{2}$ and when placed at a distance of 15 mm between transmitter and receiver, they have measured FoM values of 0.71 and 1.07 at 440 MHz and 918 MHz, respectively. The results were compared with related works found in the literature, and indicate a $η _{WPT}$ of 40.9% and 49.2 %.